GAMBARAN PENGETAHUAN GIZI, POLA MAKAN, AKTIVITAS FISIK DAN STATUS GIZI PADA SISWA - Hanny Mustika, Fielsa; Jodiono; Moviana, Yenny (Poltekkes Kemenkes Bandung, 2025)
Nutrition knowledge is one of the main factors influencing an individual's nutritional status. Unhealthy eating patterns can be a major cause of overweight and obesity, such as consuming large portions frequently, eating high-calorie and high-fat foods, and having a low-fiber diet. In addition to eating habits, a lack of physical activity also plays a significant role in the development of overweight and obesity. This study was conducted to examine the nutritional knowledge, eating patterns, physical activity, and nutritional status of students at SMA Negeri 1 Cilimus. The method used was a cross-sectional study with a simple random sampling technique, involving 34 students. The data collected included student characteristics, nutritional knowledge, eating patterns, physical activity, and their nutritional status. From the descriptive analysis, it was found that approximately 94.1% of students had inadequate nutrition knowledge, and their eating patterns were also classified as poor. Approximately 70.6% of students engaged in light physical activity. Additionally, around 23.5% of students were classified as overweight. Most of those with excess weight also had inadequate nutrition knowledge, approximately 21.9%. Similarly, those with unhealthy eating patterns and light physical activity showed overweight proportions of 21.9% and 20.8%, respectively. It is important to conduct nutrition education activities that explain balanced nutrition guidelines, proper eating patterns, the importance of physical activity, and age-appropriate nutritional needs to improve students' knowledge, nutritional status, and overall health